Investigation of Genetic Polymorphisms of CSN1S1 and BLG Genes in Norduz sheep by PCR-RFLP method - Çak, B; Yılmaz, O; Demirel, AF (Journal of the Hellenic Veterinary Medical Society, 2024)
This study was undertaken to examine genetic polymorphisms of Alpha-S1 casein (CSN1S1) and β-Lactoglobulin (BLG) genes in Norduz sheep by PCR-RFLP method. In the study, 10 ml blood samples were taken from 102 heads of Norduz sheep into tubes with EDTA. DNA isolation from blood samples was done with ready-made commercial kits. The target DNA region of alpha-s1 casein and beta-lactoglobulin genes was amplified by PCR technique. The obtained PCR patterns were digested with MboII and RsaI restriction enzymes to determine the genotypes of Alpha-S1 casein and β-lactoglobulin genes, respectively. The cut fragments were run on 2% agarose gel electrophoresis and genotypes were determined under UV light. Statistical analysis, after calculating allele and genotype frequencies by direct gene counting method, the distribution of observed and expected genotypic frequencies was determined according to the Hardy-Weinberg Equilibrium, and whether it was compatible with the χ2 test. β-Lactoglobulin AA, AB and BB genotype frequencies were found to be 17.6%, 69.6 and 12.7%, respectively. It was determined that the β-Lactoglobulin gene was not in Hardy-Weinberg Equilibrium. AlphaS1-Casein AA, AC and CC genotype frequencies were determined as 0.0, 2.9 and 97.1%, respectively. The Alpha-S1 casein gene was determined to be in Hardy-Weinberg equilibrium. It was determined that Norduz sheep showed polymorphism in terms of Alpha-S1 Casein and β-Lactoglobulin genes. In conclusion, it was determined that the A allele of the β-Lactoglobulin gene and the AB genotype were more common, the C allele and the CC genotype of the Alpha-S1 casein gene were more common, and the AA genotype was absent in Norduz sheep. It was concluded that it would be useful to investigate the economic effects of genetic polymorphisms of Alpha-S1 casein and β-Lactoglobulin genes on various yield traits in larger Norduz sheep populations.